The Fringes of Empires: Recent Scholarship on Colonial Frontiers and Borderlands in Latin America - Prado, Fabrício Pereira (History compass, 2012)
This article examines recent historical literature on colonial frontiers and borderlands in Latin America. The article explores definitions and subtleties related to the translation of the terms frontier and borderlands from Spanish/Portuguese into English. Moreover, special attention is paid the scholarship on African and Indigenous slavery in frontiers, the interaction between indigenous groups and colonists, the social importance of mestizos and go betweens, and the relationship between social groups and the environment. Most of the works reviewed present interdisciplinary approaches, including but not limited to ethnohistory, environmental studies, anthropology, sociology, cartography, humans geography, Atlantic World history.